2023
DOI: 10.1155/2023/8248948
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Nurses’ Adherence to Ethical Codes and Its Association with Spiritual Well-Being and Moral Sensitivity

Marzieh Momennasab,
Zohreh Homayoon,
Camellia Torabizadeh

Abstract: Background. Adherence to ethical codes is a major pillar of nursing care that is affected by various factors. Identifying these factors can lead to better ethical performance. The present study was conducted to determine critical care nurses’ adherence to ethical codes and its association with spiritual well-being (SWB) and moral sensitivity (MS). Methods. In this descriptive-correlational study, data were collected using the moral sensitivity questionnaire (MSQ) by Lützén et al., Paloutzian and Ellison’s spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…This study was supported by a study in Gambia (2018) which found that educational level affected the proper practicing code of ethics among nurses (Bah & Sey-Sawo, 2018 However, the current finding was incongruent with the Egyptian study in 2016 which found that the nurses had adequate practice of the professional code of ethics among nurses in outpatient and hemodialysis units (Hafez et al, 2016;Ali et al, 2018). The present study also disagreed with other studies in Iran (2016 and 2023) (Momennasab et al, 2016;Momennasab et al, 2023), Ethiopia (2022) (Haile, 2022) and Indonesia (2020) (Safitri et al, 2020), which found that nurses' adherence to NECP was at a satisfactory level.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…This study was supported by a study in Gambia (2018) which found that educational level affected the proper practicing code of ethics among nurses (Bah & Sey-Sawo, 2018 However, the current finding was incongruent with the Egyptian study in 2016 which found that the nurses had adequate practice of the professional code of ethics among nurses in outpatient and hemodialysis units (Hafez et al, 2016;Ali et al, 2018). The present study also disagreed with other studies in Iran (2016 and 2023) (Momennasab et al, 2016;Momennasab et al, 2023), Ethiopia (2022) (Haile, 2022) and Indonesia (2020) (Safitri et al, 2020), which found that nurses' adherence to NECP was at a satisfactory level.…”
Section: Discussioncontrasting
confidence: 58%
“…A similar finding was found in studies in Egypt ( 2015 However, regarding provision of nursing care practice, a significantly higher adherence to NCEP was noticed among nurses in critical care units compared to medical-surgical care units, especially in helping patient decision making and correct provision of care, in a timely manner and cooperating with other health care providers. These findings were not surprising because patients in critical care units are highly vulnerable, requiring complex care and rapid response compared to other hospital wards (Momennasab et al, 2023).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations